2016
DOI: 10.1016/j.jagp.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual Trajectories of Depression and Cognition: A Longitudinal Population-Based Study

Abstract: Objectives To examine the relationships over time between dual trajectories of depressive symptoms and several cognitive domains. Design 5-year longitudinal study. Setting Population-based cohort. Participants 1978 randomly selected individuals aged 65+ years at recruitment and assessed annually. Measurements Repeated measures of (1) depressive symptoms on the modified Center for Epidemiologic Studies-Depression Scale; (2) composite scores in the cognitive domains of attention, executive function, memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Furthermore, immediate recall score classified correctly 56% of the participants according to the absence or presence of depressive symptoms. Some studies highlight the effect of depressive symptoms in cognition (Graziane, Beer, Snitz, Chang, & Ganguli, 2016). Depressive symptoms may be correlated to a lower attention level, which directly impacts acquisition and storage of verbal information, and attention level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, immediate recall score classified correctly 56% of the participants according to the absence or presence of depressive symptoms. Some studies highlight the effect of depressive symptoms in cognition (Graziane, Beer, Snitz, Chang, & Ganguli, 2016). Depressive symptoms may be correlated to a lower attention level, which directly impacts acquisition and storage of verbal information, and attention level.…”
Section: Discussionmentioning
confidence: 99%
“…To identify distinct trajectory patterns of depressive symptoms and attention/executive function, we used a latent group-based dual trajectory modeling approach under the assumption that the sample is drawn from a discrete set of subpopulations, each one having a distinct trajectory pattern, to approximate an underlying continuous distribution with a complex structure (Graziane et al 2016; Jones and Nagin 2007; Jones et al 2001; Nagin and Odgers 2010; Nagin and Tremblay 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Depressive symptoms are risk factors for cognitive impairment (Barnes et al 2006; Saczynski et al 2010; Rosenberg et al 2010). Graziane et al (2016) found that those with moderate-grade depressive symptoms were at high risk of persistently lower cognitive function over a 5-year period. While the relationship between depressive symptoms and cognitive deficit in older adults is established, the effect of depression on cognitive function in vulnerable populations, such as persons living with HIV (PLWH), has not been well described.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…If late‐life depression is a prodromal indicator of underlying neuropathology, then differences in patterns of antecedent depressive symptoms may relate to different subtypes of cognitive decline (e.g., amnestic vs. dysexecutive). However, few studies (Paterniti et al ; Singh‐Manoux et al ; Kohler et al ; Graziane et al ) have examined how LLD patterns relate to subsequent cognitive decline by domain. In one example (Paterniti et al ), cognitively normal older adults with persistent, but not variable, depressive symptoms showed greater cognitive decline compared with those with no depression; however, domain‐specific associations were not examined.…”
Section: Introductionmentioning
confidence: 99%